Thrombolysis after cardiopulmonary resuscitation in myocardial infarction with abdominal pain as the first presentation - Yang-Jian Zheng, MD; Wen-na Wang, MD; Han-li Lin, MD; Ya-nan Wu, MD; Maya Saranathan. (Medicine, 2022)
Abstract. Rationale:. Thrombolysis after cardiopulmonary resuscitation in patients with acute ST-segment elevation myocardial infarction (STEMI) is controversial. This case report describes a successful thrombolysis after resuscitation in delayed-diagnosis STEMI. Patient concerns:. A 58-year-old man presented with acute abdominal pain as the first symptom of a subsequent STEMI diagnosis. When he returned to the clinic after having been assisted with abdominal pain relief, he suffered a sudden cardiac arrest. Cardiopulmonary resuscitation was performed immediately, and thrombolysis was carried out for his anterior STEMI. He was successfully resuscitated in a short period of time. Diagnosis:. The patient was diagnosed with acute and extensive anterior STEMI. The D-dimer level was normal, and pericardial effusion was ruled out. Interventions:. After successful resuscitation, the patient received half-dose alteplase thrombolytic therapy. After a few days, the patient was transferred to a general ward. Coronary angiography revealed unobstructed flow in the left anterior descending artery. Outcomes:. The ST segment of the patient gradually declined after thrombolytic therapy, and the myocardial injury marker levels increased. A small amount of pleural fluid in the lungs and pulmonary infection were observed. With effective diuretic, anti-infective, and other treatments, the patient's condition gradually improved, the ventilator was removed, and vasoactive drugs were successfully discontinued. Coronary angiography revealed that the flow of the culprit artery was unobstructed, and a drug-coated balloon was implanted. No wall motion abnormalities were detected on echocardiography, and the patient recovered well. Conclusions:. In patients with abdominal pain as the first presentation, a simple initial electrocardiogram may help reduce the risk of missed STEMI diagnosis. Thrombolysis after successful resuscitation is an effective treatment for these patients. However, the effects of thrombolysis after resuscitation remain unclear. The point of dispute lies in the effectiveness and safety of thrombolysis (primarily for bleeding). Prompt thrombolysis would lead to a better prognosis if spontaneous circulation can be restored within 10 minutes.